Linking Wise Organizations to Wise Leadership, Job Satisfaction, and Well-Being - Ardelt, Monika; Sharma, Bhavna (Frontiers in Communication, 2021)
Objective: Research shows that wisdom benefits individuals, but is this also true for organizations? To answer this question, we first delineated the characteristics of wise and not-so-wise organizations in the areas of goals, approach, range, characteristics of leaders and employees, and perception of aging, using a framework derived from comparing wisdom with intellectual knowledge. Guided by this framework, we then tested whether wise organizations have a positive effect on employees’ physical and subjective well-being mediated by wise leadership and job satisfaction. Method: We created a wise organization index for nine organizations from the 2007-2008 Age and Generations Study based on 74 to 390 average employees’ ratings of perceived work opportunities for training and development, flexibility at work, absence of time pressure at work, work-life balance, satisfaction with work benefits, job security, and job opportunities. A mediated path model was analyzed to test the hypothesis. The sample contained 821 employees (age range 19-74 years; M=41.98, SD=12.26) with valid values on wise (fair and supportive) leadership at the first wave of data collection and employee job satisfaction (career as calling, satisfaction with career progress, engagement at work, and organizational commitment) and physical and subjective well-being at the second wave of data collection at least six months later. Findings: Results confirmed that the positive associations between the organizations’ overall wisdom index and employees’ physical and subjective well-being scores at Wave 2 was mediated by employees’ perception of wise leadership at Wave 1and employee job satisfaction at Wave 2. Originality/value: This study fills a gap in the organizational wisdom literature by (1) systematically contrasting the characteristics of wise organizations with not-so-wise organizations, (2) creating a novel wise organization index, and (3) testing the effects of wise organizations and wise leadership on employees’ job satisfaction and physical and subjective well-being. Practical and societal implications: The results suggest that wise organizations encourage wise leadership, and wise leadership, in turn, fosters job satisfaction, which benefits employees’ physical and subjective well-being. Hence, wise organizations ultimately enhance workers’ well-being, which likely contributes to the success and reputation of the organization through higher employee productivity and better customer service.